2013
DOI: 10.1021/es3048202
|View full text |Cite
|
Sign up to set email alerts
|

Historical Trends of Atmospheric Black Carbon on Tibetan Plateau As Reconstructed from a 150-Year Lake Sediment Record

Abstract: Black carbon (BC) is one of the key components causing global warming. Especially on the Tibetan Plateau (TP), reconstructing BC's historical trend is essential for better understanding its anthropogenic impact. Here, we present results from high altitude lake sediments from the central TP. The results provide a unique history of BC over the past 150 years, from the preindustrial to the modern period. Although BC concentration levels in the Nam Co Lake sediments were lower than those from other high mountain l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
124
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(136 citation statements)
references
References 57 publications
11
124
1
Order By: Relevance
“…The blank samples (n ¼ 10) yielded 0.00 ± 0.00 mg/cm 2 for BC, and the RSD of 10 pairs of replicate analyses was in the range of 0e11%, and averaged within 5%. The BC concentration measured in SRM 1941b was 10.56 ± 1.28 mg/g (n ¼ 10), which was well in accordance with the values reported by recent studies (Hammes et al, 2007;Han et al, 2007a;Cong et al, 2013;Fang et al, 2015). These QA/QC results suggested that the BC analytical method used here was credible and repeatable (see Supplementary materials).…”
Section: Analytical Proceduressupporting
confidence: 90%
See 1 more Smart Citation
“…The blank samples (n ¼ 10) yielded 0.00 ± 0.00 mg/cm 2 for BC, and the RSD of 10 pairs of replicate analyses was in the range of 0e11%, and averaged within 5%. The BC concentration measured in SRM 1941b was 10.56 ± 1.28 mg/g (n ¼ 10), which was well in accordance with the values reported by recent studies (Hammes et al, 2007;Han et al, 2007a;Cong et al, 2013;Fang et al, 2015). These QA/QC results suggested that the BC analytical method used here was credible and repeatable (see Supplementary materials).…”
Section: Analytical Proceduressupporting
confidence: 90%
“…In this study, char and soot were measured using the IMPROVE thermal optical method according to Han et al (2007b), which has been validated and successfully applied in aerosol studies (Han et al, 2010;Lim et al, 2012) and in soil and sediment studies (Han et al, 2009(Han et al, , 2011(Han et al, , 2015a(Han et al, , 2015bCong et al, 2013), in order to yield a better understanding of the distribution, sources and potential input pathways of char and soot within the tropical coastal system in SE Asia.…”
Section: Occurrence and Input Pathways Of Char And Soot In The Gotmentioning
confidence: 99%
“…The atmosphere over the Tibetan Plateau is less affected by human activities than urban and rural regions in the middle latitudes of the Northern Hemisphere, providing a unique opportunity to study the effects of aerosols on global and regional climates. The chemistry and optical properties of aerosols over the Tibetan Plateau have thus been the subject of increasing interest (Carrico et al, 2003;Sagar et al, 2004;Pant et al, 2006;Ming et al, 2008;Cao et al, 2009aCao et al, , 2010Wang et al, 2012;Zhao et al, 2012;Cong et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of BC are more pronounced in the Tibetan Plateau than in other areas because BC accumulates on snow and ice, which can reduce the surface albedo and consequently accelerate the melting of glaciers (Flanner et al, 2009;Xu et al, 2009;Menon et al, 2010;Xu et al, 2012). Previous studies have indicated that the main source regions of BC in the Tibetan Plateau are South and East Asia, but inconsistent results have been reported (Cao et al, 2010;Lu et al, 2012;Cong et al, 2013). Lu et al (2012) reported that BC is mainly contributed by South Asia and that the intense BC emissions in eastern China (e.g., the Sichuan Basin) could influence the Tibetan Plateau in summer, which is inconsistent with the results of Cong et al (2013) for the Nam Co region.…”
Section: Introductionmentioning
confidence: 99%
“…An inventory study suggests that the BC emissions in China and India have increased by 40 and 54 % from 2000 to 2008, respectively (Kurokawa et al, 2013). Due to general circulation patterns, the QinghaiTibetan Plateau has become a strong receptor of these high-BC source areas (Cao et al, 2010;Xia et al, 2011;Cong et al, 2013;Zhao et al, 2013). Lu et al (2012) show that south Asia and east Asia are the main source regions, accounting for 67 and 17 % of BC transported to the Himalayas and Qinghai-Tibetan Plateau on an annual basis, followed by the former USSR (∼ 8 %), Middle East (∼ 4 %), Europe (∼ 2 %), and northern Africa (∼ 1 %).…”
mentioning
confidence: 99%